Taxonomic Evaluation of the Heyndrickxia (Basonym Bacillus) sporothermodurans Group (H. sporothermodurans, H. vini, H. oleronia) Based on Whole Genome Sequences - Gregor Fiedler; Anna-Delia Herbstmann; Etienne Doll; Mareike Wenning; Erik Brinks; Jan Kabisch; Franziska Breitenwieser; Martin Lappann; Christina Böhnlein; Charles M. A. P. Franz (Microorganisms, 2021)
The genetic heterogeneity of Heyndrickxia sporothermodurans (formerly Bacillussporothermodurans) was evaluated using whole genome sequencing. The genomes of 29 previously identified Heyndrickxiasporothermodurans and two Heyndrickxia vini strains isolated from ultra-high-temperature (UHT)-treated milk were sequenced by short-read (Illumina) sequencing. After sequence analysis, the two H. vini strains could be reclassified as H. sporothermodurans. In addition, the genomes of the H.sporothermodurans type strain (DSM 10599T) and the closest phylogenetic neighbors Heyndrickxiaoleronia (DSM 9356T) and Heyndrickxia vini (JCM 19841T) were also sequenced using both long (MinION) and short-read (Illumina) sequencing. By hybrid sequence assembly, the genome of the H. sporothermodurans type strain was enlarged by 15% relative to the short-read assembly. This noticeable increase was probably due to numerous mobile elements in the genome that are presumptively related to spore heat tolerance. Phylogenetic studies based on 16S rDNA gene sequence, core genome, single-nucleotide polymorphisms and ANI/dDDH, showed that H. vini is highly related to H. sporothermodurans. When examining the genome sequences of all H.sporothermodurans strains from this study, together with 4 H. sporothermodurans genomes available in the GenBank database, the majority of the 36 strains examined occurred in a clonal lineage with less than 100 SNPs. These data substantiate previous reports on the existence and spread of a genetically highly homogenous and heat resistant spore clone, i.e., the HRS-clone.